Multimodal non-hormonal intervention with phytoestrogen nutrition and Damask rose aromatherapy improves quality of life in early menopausal women: a quasi-experimental study - Putri Dewi Anggraini; Ratih Kumala Dewi; Luluk Khusnul Dwihestie; Benedicta Audrey Putri Trisnadewi; Ratih Paramastuti (International Journal of Public Health Science (IJPHS), 2026)
Early menopause and perimenopause are increasingly recognized as critical women’s health issues due to their substantial hormonal instability, heightened symptom burden, and negative impact on quality of life. Safe non-hormonal interventions remain limited, particularly in community settings, despite growing evidence supporting phytoestrogens and mind body therapies. This study aimed to evaluate the effectiveness of a 12-week holistic intervention integrating phytoestrogen nutrition, Damask rose aromatherapy, and guided relaxation on hormonal regulation, metabolic markers, menopausal symptoms, and quality of life among early menopausal and perimenopausal women. Using a quasi-experimental design, 44 participants received soy-based dietary supplementation, nightly aromatherapy, and structured relaxation practices, with pre-post assessments of estradiol, lipid profile, fasting glucose, Menopausal Rating Scale (MRS), and Menopause-Specific Quality of Life Questionnaire (MENQOL). The intervention produced significant improvements across all domains, including increased estradiol (p < 0.001), reduced low-density lipoprotein (LDL) and fasting glucose (p = 0.001-0.003), and substantial reductions in menopausal symptoms and psychological distress (p < 0.001). Early menopausal women exhibited greater improvements, reflecting their higher biological sensitivity to multimodal interventions. These findings demonstrate the potential of integrated, non-hormonal strategies to address complex menopausal changes, with practical implications for community-based women’s health programs. Study limitations include the modest sample size and quasi-experimental design, highlighting the need for larger controlled trials.